Development of a Robust Wireless Sensor Mesh and Multi-hop Network - Mohd Taib, Ahmad Muhaimin (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Wireless networking has evolved rapidly since the first wireless device was invented. Throughout those years, researchers and engineers are struggling to apply the knowledge of wireless networking in useful ways in real life. Wireless Sensor Network (WSN) has been used in many applications, from habitat surveying to critical monitoring. Reliability of the WSN plays a major role in deciding whether it should be used or not in critical applications instead of using traditional wireless technology or wired networking. This project is solely a research and development of routing algorithm for WSN by using an existing source and straight away finding its weak point in order to apply further improvisation. The existing routing algorithms used are the XMESH and Ad-Hoc On-Demand Vector Routing (AODV).